Adeno-associated virus vectored immunoprophylaxis to prevent HIV in healthy adults: a phase 1 randomised controlled trial. Issue 4 (April 2019) - Priddy, Frances H; Lewis, David J M; Gelderblom, Huub C; Hassanin, Hana; Streatfield, Claire; LaBranche, Celia; Hare, Jonathan; Cox, Josephine H; Dally, Len; Bendel, Daryl; Montefiori, David; Sayeed, Eddy; et al.
Summary: Background: A preventive vaccine for HIV is a crucial public health need; adeno-associated virus (AAV)-mediated antibody gene delivery could be an alternative to immunisation to induce sustained expression of neutralising antibodies to prevent HIV. We assessed safety and tolerability of rAAV1-PG9DP, a recombinant AAV1 vector encoding the gene for PG9, a broadly neutralising antibody against HIV. Methods: This first-in-human, proof-of-concept, double-blind, phase 1, randomised, placebo-controlled, dose-escalation trial was done at one clinical research centre in the UK. Healthy men aged 18–45 years without HIV infection were randomly assigned to receive intramuscular injection with rAAV1-PG9DP or placebo in the deltoid or quadriceps in one of four dose-escalating cohorts (group A, 4 × 10 12 vector genomes; group B, 4 × 10 13 vector genomes; group C, 8 × 10 13 vector genomes; and group D, 1·2 × 10 14 vector genomes). Volunteers were followed up for 48 weeks. The primary objective was to assess safety and tolerability. A secondary objective was to assess PG9 expression in serum and related HIV neutralisation activity. All volunteers were included in primary and safety analyses. The trial is complete and is registered withClinicalTrials.gov, numberNCT01937455 . Findings: Between Jan 30, 2014, and Feb 28, 2017, 111 volunteers were screened for eligibility. 21 volunteers were eligible and provided consent, and all 21 completed 48 weeks of follow-up. Reactogenicity was generally mild or moderate and resolved without intervention. No probably or definitely related adverse events or serious adverse events were recorded. We detected PG9 by HIV neutralisation in the serum of four volunteers, and by RT-PCR in muscle biopsy samples from four volunteers. We did not detect PG9 by ELISA in serum. PG9 anti-drug antibody was present in ten volunteers in the higher dose groups. Both anti-AAV1 antibodies and AAV1-specific T-cell responses were detected. Interpretation: Future studies should explore higher doses of AAV, alternative AAV serotypes and gene expression cassettes, or other broadly neutralising HIV antibodies. Funding: International AIDS Vaccine Initiative, United States Agency for International Development, Bill & Melinda Gates Foundation, US National Institutes of Health.